Carbon material, positive electrode for power storage device, negative electrode using the same, and power storage device

By using carbon materials with specific structure and performance as lithium-ion battery electrodes, the battery life shortening caused by negative electrode expansion and positive electrode lattice changes is solved, and the battery conductivity and durability is improved. It is suitable for high mechanical stress environments such as electric vehicles.

JP7626509B2Active Publication Date: 2025-02-043DC INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024510470
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-07-25
Publication Date
2025-02-04
Estimated Expiration
2043-07-25

AI Technical Summary

Technical Problem

The negative electrode materials of existing lithium-ion batteries shorten their life due to the expansion of silicon particles during charging and discharging. The lattice changes of the positive electrode materials increase resistance, affecting battery performance, and the electrode resistance increases under mechanical stress, especially in electric vehicle applications.

Method used

Carbon materials with specific structures and properties are used as electrode materials, including carbon materials with volume elasticity less than 2GPa, average graphene grid size greater than 50nm, graphene network nitrogen content less than 10wt%, BET specific surface area 400-2600m²/g, few edge sites, and porous structures to enhance the flexibility and conductivity of the electrode.

Benefits of technology

It improves the conductivity and durability of the battery, reduces the resistance changes under mechanical stress, and extends the battery life. It is suitable for high mechanical stress environments such as electric vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626509000006
    Figure 0007626509000006
  • Figure 0007626509000007
    Figure 0007626509000007
  • Figure 0007626509000008
    Figure 0007626509000008
Patent Text Reader

Abstract

The purpose of the present invention is to provide a carbon material with which high conductivity and durability can be achieved along with compressive flexibility, as well as an electrical storage device that has said carbon material contained inside an electrode. The present invention provides a carbon material that has a bulk elastic modulus K of 2 GPa or less and an average graphene lattice size L of 50 nm or greater. The present invention also provides a positive electrode (212) for an electrical storage device and a negative electrode (214) for an electrical storage device, wherein said carbon material is used as a conductivity aid, as well as an electrical storage device (200) that is provided with a positive electrode and / or a negative electrode including said carbon material as a conductivity aid.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbon material and a conductive assistant using the same. [Background technology]

[0002] In recent years, efforts to realize a sustainable society have been attracting attention. In particular, research and development aimed at achieving carbon neutrality, which means reducing greenhouse gas emissions to zero overall, has been actively carried out, and research into new carbon materials aimed at improving the performance of power storage devices such as secondary batteries and electric double-layer capacitors (EDLCs) is being conducted globally.

[0003] Carbon materials, including graphene, have excellent thermal conductivity, electrical conductivity, and mechanical (tensile) strength, and are being researched for applications in various fields such as electronics and energy materials. In particular, porous carbon materials are being actively researched as catalysts for reaction fields due to their large specific surface area, and as electrodes and related materials for energy devices such as batteries and capacitors due to their electrical conductivity. Summary of the Invention [Problem to be solved by the invention]

[0004] One promising application of conductive, porous, and flexible carbon materials is lithium-ion batteries, which use silicon for the negative electrode. It has been pointed out that the charge-discharge cycle characteristics of lithium-ion batteries are such that the silicon particles in the negative electrode active material expand with repeated charge and discharge, resulting in a deterioration in the battery's lifespan. If this expansion of microscopic silicon particles could be absorbed by compressing flexible particles, this problem would be solved. However, there is still insufficient knowledge about flexibility against compression, and there is a problem in that guidelines for parameters and design related to flexibility have not yet been obtained.

[0005] In addition, the positive electrode, the other main component of a lithium-ion battery, does not undergo volumetric changes during charging and discharging as much as the negative electrode, but microscopically, the dimensions of the crystal lattice definitely change as lithium ions are inserted and removed. case It is self-evident that micro-motion caused by dimensional changes in the electrodes will ultimately cause an increase in the resistance of the electrodes, affecting the charge / discharge life.

[0006] Furthermore, the range of uses for lithium-ion batteries is expanding from power sources for portable devices to power sources for electric vehicles (EVs). Under these circumstances, there are still insufficient measures to prevent the effect of mechanical stress, which is an external factor of the battery, on the increase in electrode resistance, including the adverse effect on battery life caused by vehicle body vibrations while the EV is running, and this is also a major issue.

[0007] The present invention has been made in consideration of the above circumstances, and aims to provide a carbon material and an electricity storage device containing the same inside an electrode, which can obtain high electrical conductivity and durability as well as flexibility against compression caused by stress generated by macroscopic and / or microscopic mechanical vibrations occurring inside and outside the battery. [Means for solving the problem]

[0008] As a result of extensive research, the inventors have discovered a bulk modulus K, which is an index related to flexibility, and have found that a carbon material having excellent flexibility against compression, electrical conductivity, and durability can be realized when the bulk modulus K is 2 GPa or less and the average graphene network plane size L is 50 nm or more.

[0009] In order to solve the above problems, the present invention provides the following configuration. (1) A carbon material having a bulk modulus K of 2 GPa or less and an average graphene network plane size L of 50 nm or more.

[0010] (2) The carbon material according to (1), wherein the average number of layers, n, is 1 or more and 6 or less.

[0011] (3) The carbon material according to (1) or (2), having a pore diameter d of 5 nm or more and 65 nm or less.

[0012] (4) The carbon material according to any one of (1) to (3), in which the nitrogen content N in the graphene network plane is 0 wt % or more and 10 wt % or less.

[0013] (5) BET specific surface area S is 400m 2 / g or more 2600m 2 / g or less of the carbon material (1) to (4).

[0014] (6) Edge site amount N edge The carbon material according to any one of (1) to (5), wherein the carbon content is 500 μmol / g or less.

[0015] (7) Edge site specific surface area S edge 30m 2 / g or less of the carbon material (1) to (6).

[0016] (8) Pore volume V total is 1.9cm 3 / g or more 5cm 3 / g or less of the carbon material (1) to (7).

[0017] (9) A negative electrode for an electricity storage device, which uses any one of the carbon materials according to (1) to (8) as a conductive additive.

[0018] (10) A positive electrode for an electricity storage device, which uses any one of the carbon materials according to (1) to (8) as a conductive additive.

[0019] (11) An electricity storage device having a positive electrode and / or a negative electrode in which the carbon material according to any one of (1) to (8) is used as a conductive additive. Effect of the Invention

[0020] According to the present invention, it is possible to provide a carbon material that has flexibility against compression as well as electrical conductivity and durability, and a long-life electricity storage device that uses the carbon material at least as a conductive assistant for a positive electrode and / or a negative electrode. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a perspective view showing an example of a configuration of a carbon material according to an embodiment of the present invention. [Diagram 2] 1 is a flowchart illustrating an example of a method for producing a carbon material according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a diagram for explaining a method for producing a carbon material according to one embodiment of the present invention, showing the state of a coating step. [Figure 4] FIG. 2 is a diagram for explaining a method for producing a carbon material according to one embodiment of the present invention, showing the state of a separation step. [Figure 5A] 1 is a graph showing the results of mercury intrusion measurement in Example 1. [Figure 5B] 1 is a graph showing the results of mercury intrusion measurement in Example 2. [Figure 5C] 1 is a graph showing the results of mercury intrusion measurement in Example 3. [Figure 5D] 1 is a graph showing the results of mercury intrusion measurement in Example 4. [Figure 5E] 1 is a graph showing the results of mercury intrusion measurement in Reference Example 1. [Figure 6A] 1 is a graph showing the results of mercury intrusion measurement in Comparative Example 1. [Figure 6B] 1 is a graph showing the results of mercury intrusion measurement in Comparative Example 2. [Figure 6C] 1 is a graph showing the results of mercury intrusion measurement in Comparative Example 3. [Figure 7A] 1 is a graph showing the results of mercury intrusion measurement in Comparative Example 4. [Figure 7B] 13 is a graph showing the results of mercury intrusion measurement in Comparative Example 5. [Figure 7C] 1 is a graph showing the results of mercury intrusion measurement in Comparative Example 6. [Figure 7D] 1 is a graph showing the results of mercury intrusion measurement in Comparative Example 7. [Figure 7E] 13 is a graph showing the results of mercury intrusion measurement in Comparative Example 8. [Figure 8A] 13 is a graph showing the results of mercury intrusion measurement in Comparative Example 9. [Figure 8B] 1 is a graph showing the results of mercury intrusion measurement in Comparative Example 10. [Figure 8C] 1 is a graph showing the results of mercury intrusion measurement in Comparative Example 11. [Figure 9] FIG. 1 is a diagram illustrating an ultra-high sensitivity vacuum TPD instrument 60 used in thermal desorption analysis. [Figure 10A] 1 shows a gas emission pattern when a thermal desorption analysis was carried out in Example 1. [Figure 10B] 1 shows a gas emission pattern when a thermal desorption analysis was carried out in Example 2. [Figure 10C] 1 shows a gas emission pattern when a thermal desorption analysis was carried out in Example 3. [Figure 10D] 1 shows a gas emission pattern when a thermal desorption analysis was carried out in Example 4. [Figure 10E] 1 shows a gas emission pattern when a thermal desorption analysis was carried out in Reference Example 1. [Figure 11A] 4 shows a gas discharge pattern in Comparative Example 1. [Figure 11B] 4 shows a gas discharge pattern in Comparative Example 2. [Figure 11C] 13 shows a gas discharge pattern in Comparative Example 3. [Figure 12A] 13 shows a gas discharge pattern in Comparative Example 4. [Figure 12B] 11 shows a gas discharge pattern in Comparative Example 5. [Figure 12C] 13 shows a gas discharge pattern in Comparative Example 6. [Figure 12D] 13 shows a gas discharge pattern in Comparative Example 7. [Figure 12E] 13 shows a gas discharge pattern in Comparative Example 8. [Figure 13A] 13 shows a gas discharge pattern in Comparative Example 9. [Figure 13B] 13 shows a gas discharge pattern in Comparative Example 10. [Figure 13C] 13 shows a gas discharge pattern in Comparative Example 11. [Figure 14A]1 shows nitrogen adsorption / desorption isotherms for Examples 1 to 4 and Reference Example 1. [Figure 14B] 1 shows nitrogen adsorption / desorption isotherms for Comparative Examples 1 to 3. [Figure 14C] 1 shows nitrogen adsorption / desorption isotherms for Comparative Examples 4 to 8. [Figure 14D] 13 is a nitrogen adsorption / desorption isotherm for Comparative Example 9. [Figure 14E] 1 shows nitrogen adsorption / desorption isotherms for Comparative Examples 10 and 11. [Figure 15A] FIG. 1 is a schematic diagram of the adsorption isotherm of type I. [Figure 15B] FIG. 1 is a schematic diagram of the adsorption isotherm of Type IV. [Figure 16A] 1 shows the pore size distributions of Examples 1 to 4 and Reference Example 1. [Figure 16B] 4 shows pore size distributions of Comparative Examples 1 to 3. [Figure 16C] 4 shows the pore size distributions of Comparative Examples 4 to 8. [Figure 16D] 13 is the pore size distribution of Comparative Example 9. [Figure 16E] 1 shows the pore size distributions of Comparative Examples 10 and 11. [Figure 17] 1 is a graph showing the relationship between the bulk modulus K and the structural characteristics of Examples 1 to 4, Reference Example 1, and Comparative Examples 1 to 11. [Figure 18A] 1 is an SEM image of Example 1. [Figure 18B] 1 is an SEM image of Comparative Example 2. [Figure 18C] 1 is an SEM image of Comparative Example 3. [Figure 18D] 1 is an SEM image of Comparative Example 4. [Figure 19] 1 shows Raman spectra of Examples 1 to 4 and Reference Example 1. [Figure 20] 1 is a diagram showing an example of a cross-sectional structure of an electricity storage device according to an embodiment of the present invention; [Figure 21] FIG. 2 is a graph comparing the relationship between the amount (wt%) of a conductive assistant added to a positive electrode and the charge / discharge capacity (mAh) between Examples and Comparative Examples. [Figure 22]FIG. 2 is a graph comparing the relationship between the amount (wt %) of a conductive assistant in a negative electrode and the charge / discharge capacity (mAh) between Examples and Comparative Examples. [Diagram 23] FIG. 1 is a graph comparing the relationship between the amount of conductive additive added in the positive electrode and the initial efficiency, and the relationship between the amount of conductive additive added and the 10-cycle retention rate, between Examples and Comparative Examples. [Figure 24] FIG. 11 is a graph comparing the relationship between the amount of conductive additive added in the negative electrode and the initial efficiency, and the relationship between the amount of conductive additive added and the retention rate at the 10th cycle between Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] An example of an embodiment of the present invention will be described below. The present invention is not limited to the following example. The drawings used in the following description are schematic diagrams in which characteristic parts are enlarged for the sake of convenience in order to make the features of the present invention easier to understand. Therefore, the number of components, dimensional ratios, etc. may differ from the actual ones. The materials, dimensions, numbers, etc. exemplified in the following description are examples, and the present invention is not limited to them, and can be appropriately changed and implemented within the scope that does not change the gist of the present invention.

[0023] [Carbon materials] FIG. 1 is a perspective view showing an example of the configuration of a carbon material according to an embodiment of the present invention. The carbon material 100 shown in FIG. 1 has a bulk modulus K of 2 GPa or less and an average graphene network surface size L of 50 nm or more. The carbon material 100 has, for example, a three-dimensional porous structure. The carbon material 100 has, for example, a graphene skeleton 10. The graphene skeleton 10 is composed of, for example, a plurality of graphene sheets 1. It is confirmed that the carbon material 100 has a graphene skeleton by Raman spectroscopy. The carbon material 100 has, for example, a pore structure corresponding to the shape of template nanoparticles described later.

[0024] The smaller the bulk modulus K of the carbon material 100, the higher the mechanical flexibility. It is preferably 1.5 GPa or less, more preferably 1.0 GPa or less, and even more preferably 0.7 or less. Here, in this embodiment, the bulk modulus K is calculated by mercury intrusion measurement. In this embodiment, the mechanical flexibility is an index related to the resistance to fracture when a mechanical stress is applied to the carbon material.

[0025] The average graphene mesh plane size L of the carbon material 100 is preferably 70 nm or more, more preferably 100 nm or more, and even more preferably 150 nm or more. The larger the average graphene mesh plane size L of the carbon material 100, the smaller the amount of edge sites, which increases the durability of the structure and improves the energy density when used in an energy storage device. The average graphene mesh plane size L of the carbon material 100 is the average value of the size in the spreading direction of graphene in multiple graphene sheets 1 contained in the graphene skeleton 10 constituting the carbon material 100. The average graphene mesh plane size L of the carbon material 100 is calculated by multiplying the edge site amount N of the carbon material 100 measured by a temperature programmed desorption method by the amount of edge sites N edge (μmol / g) and basal site amount N basal The carbon material 100 has a large graphene network surface size L, and therefore when applied to an electrode of an electric double layer capacitor (EDLC), the electrolyte is less likely to decompose even when a high voltage is applied, and a high voltage can be applied, which can further improve the energy density and reliability.

[0026] Edge site amount N of carbon material 100 edge is, for example, 600 μmol / g or less, preferably 500 μmol / g or less, more preferably 300 μmol / g or less, and may be 250 μmol / g or less, or 150 μmol / g or less. edgeIf the capacitance is small, the effect is particularly easily obtained when the material is applied to an electrode of an EDLC as described in the previous paragraph.

[0027] Edge site specific surface area S of carbon material 100 edge For example, 100m 2 / g or less, 30m 2 / g or less, and 2 / g or less is more preferable, m 2 / g More preferably, it is 10 m 2 / g It may be the following.

[0028] The carbon material 100 is composed of, for example, a porous carbon material. In the carbon material 100, each of the graphene sheets 1 constituting the graphene skeleton 10 includes a structure other than a six-membered ring. Specifically, each of the graphene sheets 1 includes, for example, at least one selected from the group consisting of a five-membered ring, a seven-membered ring, and an eight-membered ring. When the graphene sheets 1 include a structure other than a six-membered ring, the planar network of the graphene skeleton is distorted, and a three-dimensional porous structure of the carbon material 100 as shown in FIG. 1 is formed.

[0029] The nitrogen content N in the graphene network plane of the carbon material 100 is, for example, 0 wt% or more and 20 wt% or less, preferably 0 wt% or more and 10 wt% or less, and more preferably 0 wt% or more and 5 wt% or less. The nitrogen content N in the graphene network plane of the carbon material 100 may be 0 wt%. It is preferable from the viewpoint of flexibility that the nitrogen content N in the graphene network plane of the carbon material 100 is within the above range. The nitrogen content N in the graphene network plane of the carbon material 100 is measured by a method such as organic element analysis, X-ray photoelectron spectroscopy, or TPD measurement.

[0030] The BET specific surface area S of the carbon material 100 is, for example, 400 m 2 / g or more 2600m 2 / g or less, 1000m 2 / g or more, 1500m 2 / g or more 2600m 2 / g or less, and 2 / g or more 2600m 2 It is more preferable that the molecular weight is not more than 1 / g.

[0031] The average number of layers n of the carbon material 100 is, for example, 1 or more and 6 or less, preferably 1 or more and 3 or less, and more preferably 1 or more and 2 or less. The average number of layers n of the carbon material 100 is determined by the basal specific surface area S basal The theoretical specific surface area of ​​graphene S graphene (2627m 2 / g), the average number of carbon layers n can be calculated. Basal specific surface area S basal is the specific surface area S and S edge The difference is the specific surface area. S is the specific surface area of ​​the carbon material 100, and is calculated from the nitrogen adsorption isotherm.

[0032]

number

[0033] The pore diameter d of the carbon material 100 is, for example, 1 nm or more and 100 nm or less, preferably 5 nm or more and 65 nm or less, and may be 20 nm or less, 15 nm or less, or 12 nm or less. The pore diameter d of the carbon material 100 is calculated by the BJH method in accordance with JISZ8831-2:2010 or the DFT method in accordance with JISZ8831-3:2010. Since the BJH method can accurately measure pore diameters, particularly those of 2 to 50 nm, the calculation of pore diameters in this range is performed by the BJH method, and pore diameters outside this range are calculated by the DFT method. That is, when the pore diameter is calculated to be less than 2 nm or greater than 50 nm by the BJH method, the pore diameter is calculated by the DFT method. The pore diameter d can be adjusted, for example, by the particle size of the nanoparticles that make up the template.

[0034] The pore volume Vtotal of the carbon material 100 is, for example, 1.3 cm3 / g or more 5cm 3 / g or less, and 1.9 cm 3 / g or more 5cm 3 / g or less, and 2.5 cm 3 / g or more 5cm 3 The pore volume of the carbon material 100 is calculated by nitrogen adsorption / desorption measurement.

[0035] A carbon material according to one embodiment of the present invention is, for example, a porous carbon material having pores corresponding to the shape of the nanoparticles constituting the template, and has a bulk modulus K of 2 GPa or less and an average graphene network plane size L of 50 nm or more, thereby providing high mechanical flexibility as well as high electrical conductivity and durability.

[0036] [Method of manufacturing carbon materials] 2 is a flow chart showing an example of a method for producing a carbon material according to this embodiment. The method for producing a carbon material according to this embodiment further includes, for example, a coating step of coating a template with a carbon layer to obtain a molded product, a separation step of dissolving the template with an acid to separate the molded product from the template, and a stabilization step of heat-treating the molded product separated from the template by the separation step after the separation step.

[0037] <Coating process> First, a mold is coated with a carbon layer to obtain a molded product. FIG. 3 is a diagram for explaining a method for producing a carbon material according to one embodiment of the present invention, showing the state of the coating process. Specifically, FIG. 3 is a partial cross-sectional perspective view of a molded product in which a carbon layer is coated on a template nanoparticle, and a cross-sectional view enlarging the vicinity of one template nanoparticle. In the molded product 30 shown in FIG. 3, the template T is coated with a carbon layer 11 (thick black line). FIG. 3 also shows the particle size d0 of the nanoparticles of the template T.

[0038] The template T is, for example, one made of metal nanoparticles that can be dissolved in acid in the separation process. When hydrofluoric acid is used in the separation process, a template T made of nanoparticles of alumina, zeolite, or the like can be used. From the viewpoint of avoiding the use of hydrofluoric acid in the separation process, it is preferable to use a template T made of metal nanoparticles made of an oxide of an alkaline earth metal, and specifically, a template T made of nanoparticles of magnesium oxide, calcium carbonate, or calcium oxide can be used.

[0039] Coating of the carbon layer 11 on the template T may be performed by, for example, a wet method such as an impregnation method, a dry method such as a chemical vapor deposition (CVD) method, or a combination of a wet method and a dry method, in which the wet method is performed first and then the dry method. From the viewpoint of controlling the number of layers of the carbon layer 11 to be formed to one or more layers, it is preferable to utilize a chemical vapor deposition (CVD) method, which is a dry method, for coating of the carbon layer 11 in the coating step.

[0040] Hereinafter, this embodiment will be described taking as an example a means for coating the mold T with the carbon layer 11 by the CVD method to obtain the molded product 30. Coating with the carbon layer 11 by the CVD method may be performed in multiple steps.

[0041] In the coating step, organic compounds such as acetylene, methylacetylene, ethylene, propylene, isoprene, cyclopropane, methane, ethane, propane, benzene, toluene, vinyl compounds, ethylene oxide, methanol, ethanol, acetonitrile, and acrylonitrile are used as raw material gases for the CVD method. From the viewpoint of making it easier for the gas to enter the gaps G of the mold T, it is preferable to use acetylene, ethylene, propylene, methane, or ethane as the raw material gas.

[0042] When the coating step is carried out by the CVD method, the step is carried out under heating, and the heating temperature can be, for example, 400 to 1500° C., and the pressure during CVD can be, for example, 1 to 200 kPa. The temperature rise rate in the coating step is, for example, 1 to 50° C. / min.

[0043] In the coating step, in addition to the above-mentioned raw material gas, for example, an inert gas may be used as a carrier gas. In addition to the inert gas, a gas containing oxygen gas, hydrogen gas, etc. may be used as the carrier gas. In the coating step, from the viewpoint of coating one or two carbon layers 11, the flow rate of the carrier gas is preferably controlled to 0.05 to 1.00 m / min, and the amount of the raw material gas relative to the total amount of the raw material gas and the carrier gas is preferably controlled to 1 to 60 volume %.

[0044] In the case where a wet method is used in the coating step, for example, the carbonization may be performed by impregnating the carbon fiber with an organic compound.

[0045] The coating process may be performed using a nitrogen-containing solvent so that the carbon layer to be formed is doped with nitrogen. For example, the template nanoparticles T may be subjected to chemical vapor deposition by passing an inert gas through a nitrogen-containing solvent. Examples of the nitrogen-containing solvent that may be used include acetonitrile, acrylonitrile, ethylenediamine, and pyridine.

[0046] <Separation process> Next, the mold T is dissolved with an acid or the like, and the molded product 30 is separated from the mold T. FIG. 4 is a diagram for explaining a method for producing a carbon material according to an embodiment of the present invention, and shows the state of a separation step. The molded product 50 shown in FIG. 4 is a precursor of a carbon material 100 composed of a carbon layer 12. The molded product 50 shown in FIG. 4 is called a carbon meso sponge (CMS). FIG. 4 shows the pore diameter d of the molded product 50.

[0047] In the separation process, for example, inorganic acids such as hydrofluoric acid, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, boric acid, etc., organic acids having a carboxyl group, a hydroxyl group, a thiol group, an alkenol structure, etc. in the molecule, or mixtures thereof are used. When a template made of an alkaline earth metal is used as the template T, the porous template is dissolved with an acid that does not contain hydrofluoric acid. Considering safety, environmental load, and cost, it is preferable not to use hydrofluoric acid. It can be avoided by using a template made of an alkaline earth metal that can be dissolved in acids other than hydrofluoric acid, such as hydrochloric acid and sulfuric acid.

[0048] In addition, an acid containing fluorine such as hydrofluoric acid generally forms a poorly soluble compound with the alkaline earth metal contained in the alkaline earth metal oxide, and therefore forms a poorly soluble compound in the aqueous medium during the dissolution process of the alkaline earth metal oxide. In contrast, by using an acid that does not contain fluorine, it is possible to form a compound that is easily soluble in the aqueous medium without forming an insoluble salt. That is, according to this embodiment, by using an acid that does not contain hydrofluoric acid, the porous template can be easily dissolved when the alkaline earth metal oxide constituting the template T, particularly magnesium oxide or calcium oxide, is used as the template. Here, dissolving refers to the formation of a clear, transparent, uniform liquid without any insoluble compounds remaining in the aqueous medium when the template and the acid of the aqueous medium are contacted.

[0049] In the separation step, the amount of the acid used to separate the molded product 30 from the template T is, for example, 1 time or more, and preferably 1.2 times or more, based on the stoichiometric ratio of the template T. In the separation step, the temperature at which the template T is dissolved with the acid is, for example, in the range of 5 to 100° C. In the separation step, for example, the acid mixed with the porous template may be subjected to a stirring operation, a vibration operation, or the like.

[0050] In the separation step, the porous carbon material separated from the mold T can be recovered, for example, by filtration, and then dried by vacuum heating and drying to produce the porous carbon material. The molded product 50 may be recovered, for example, by suction filtration. The vacuum drying and heating to obtain the porous carbon material can be performed, for example, at a temperature of 100 to 200°C for 1 to 10 hours. In order to avoid capillary shrinkage of the molded product 50 due to vacuum drying and heating, the solvent may be replaced with a solvent having a low surface tension, such as acetone or alcohols, after the suction filtration. The molded product 50 obtained by this step is a CMS, the details of which will be described later. The degree of capillary shrinkage depends on the shape and size of the molded product 50, but it may shrink to about half.

[0051] Due to the above-mentioned capillary shrinkage, the shape of the carbon layer 12 of the molded product 50 after the separation step changes from the shape of the carbon layer 11 before the separation step, and becomes a locally distorted structure. The pore diameter d of the carbon layer 12 is smaller than the particle diameter d0 of the template nanoparticle T. In other words, the ratio d / d0 of the pore diameter d of the carbon layer 12 to the particle diameter d0 of the template nanoparticle T is less than 1.

[0052] <Stabilization process> Next, after the separation step, the molded product separated from the mold T obtained by the separation step is heat-treated. In the stabilization step, the heat treatment of the molded product can be carried out, for example, at 900 to 2000°C for 0.1 to 5 hours. The heat treatment of the molded product in the stabilization step is preferably carried out at 1600 to 1800°C for 0.5 to 2 hours.

[0053] Through the stabilization step, the carbon layer 12 of the molded product 50 expands in graphene network plane size L to become a carbon layer (graphene sheet) 1, and a carbon material 100 as shown in FIG. 1 is obtained.

[0054] The method for producing a carbon material according to the present embodiment may further include a production step not described in the above production method. For example, a heat treatment step may be included before the coating step. In addition, a hot pressing step of high-temperature compression of the molded product may be included between the separation step and the stabilization step. In addition, an adjustment step of adjusting the composition of the carbon material to be molded may be included. The adjustment step may be performed, for example, before the coating step, between the coating step and the separation step, or between the separation step and the stabilization step.

[0055] <Heat treatment process> The method for producing a carbon material according to the embodiment may have a heat treatment step of heat treating the template T before the covering step. The heat treatment of the template T is performed, for example, in an inert gas atmosphere, an air atmosphere, or a vacuum. The heat treatment of the template T is performed, for example, at 400 to 1100°C, preferably at 500 to 1000°C, and more preferably at 600 to 950°C. The heat treatment of the template T is performed, for example, for 0.1 to 3 hours, preferably for 0.2 to 1 hour. By heat treating the template T under the above conditions before the covering step, if impurities are mixed in the template T, the impurities can be decomposed. As a specific example, when the template T made of magnesium oxide is used, magnesium hydroxide and magnesium carbonate mixed in the template T are decomposed and separated from the template T by heat treatment. The above heat treatment step can increase the specific surface area S of the template T and increase the pore diameter d.

[0056] <Hot pressing process> In the hot pressing step, for example, pressure is applied to the molded product 50 while the molded product 50 is heated. Specifically, the molded product 50 is placed in a mold, and pressure is applied to the molded product 50 while the molded product 50 is heated to a high temperature. By performing the hot pressing step between the separation step and the stabilization step, a carbon material with a small pore volume can be obtained.

[0057] <Adjustment process> In the adjustment step, the composition of the carbon material is adjusted based on the following formula (2). Specifically, the manufacturing conditions are adjusted so that the graphene network plane size L of the carbon material, the average number of layers n of the carbon material, the nitrogen content N in the graphene network plane of the carbon material, the pore diameter d of the porous carbon material, and the surface tortuosity t are all desired values ​​so that the bulk modulus K is a desired value. The following formula (2) was found by the present inventors and shows the correlation between the bulk modulus of the carbon material and five variables.

[0058]

number

[0059] In the adjustment step, in formula (2), the graphene network plane size L (nm) of the carbon material is adjusted to satisfy 70≦L≦1000, and preferably adjusted to satisfy 100≦L≦1000, the average number of carbon layers n of the carbon material is adjusted to satisfy 1≦n≦6, and preferably adjusted to satisfy 1≦n≦3, the graphene network plane nitrogen content N (wt%) of the carbon material is adjusted to satisfy 0≦N≦20, and preferably adjusted to satisfy 0≦N≦10, the pore diameter d (nm) is adjusted to satisfy 1≦d≦100, and preferably adjusted to satisfy 5≦d≦70, and the surface tortuosity t is adjusted to satisfy 1.1≦t≦20, and preferably adjusted to satisfy 1.3≦t≦10. Here, when a means including a stabilization step is adopted as the method for producing the carbon material, d in the above formula (2) represents the pore diameter of the carbon material after the stabilization step.

[0060] The graphene mesh plane size L can be adjusted, for example, by adjusting the conditions of the coating step and the stabilization step in the above-mentioned production method. The graphene mesh plane size L can be increased by increasing the amount of carbon coating in the coating step and / or increasing the heating temperature or reaction time in the stabilization step. The average number of carbon layers n of the carbon material can be adjusted by, for example, adjusting the conditions of the coating step and the stabilization step in the above-mentioned production method. The average number of carbon layers n can be increased by increasing the heating temperature or reaction time in the coating step. The nitrogen content N within the graphene network plane of the carbon material is adjusted, for example, by adjusting the conditions in the coating step in the above-mentioned production method. The pore diameter d of the porous carbon material is adjusted by at least one of adjusting the template used and adjusting the conditions in the separation step. The pore diameter d can be increased by at least one of using a template with a large particle size and adjusting the drying conditions in the separation step. The surface torsion t is a variable related to the shrinkage that occurs when the template is removed and dried in the separation step. The surface torsion t is defined by the following formula (3). That is, the surface torsion t is calculated from the ratio of the surface area of ​​the template particle to the surface area of ​​a sphere assumed to have the pore size of the template graphene. The surface torsion t is adjusted by at least one of adjusting the template, adjusting the pore size d, and adjusting the average number of layers n.

[0061]

number

[0062] By the adjustment step, a carbon material having a desired graphene network plane size L and bulk modulus K can be produced.

[0063] [Design method of carbon materials] Considering the above-mentioned manufacturing method of the carbon material, it is possible to apply it to a design method for flexibility of the carbon material. For example, the following design method can be implemented.

[0064] First, in the process of setting the flexibility parameters of the carbon material, the following five parameters that constitute the bulk modulus K of the carbon material are set as the flexibility parameters of the carbon material: the graphene network plane size L of the carbon material, the average number of layers n of the carbon material, the nitrogen content N in the graphene network plane of the carbon material, the pore diameter d of the porous carbon material, and the surface torsion t.

[0065] Next, in the process of setting the flexibility of the product, the range of the bulk modulus K of the carbon material constituting the product is set.

[0066] Next, in the process of discriminating parameters, parameters specified in the product design and parameters that can be freely designed are discriminated.

[0067] Then, the freely designed parameters are set using the above formula (2) to set parameters that realize the set range of bulk modulus K. This sets the flexibility parameters of the carbon material that makes up the product.

[0068] The specific flexibility parameter is set by an adjustment process or the like in the manufacturing method of the carbon material.

[0069] Next, a lithium ion secondary battery, which is an electricity storage device of the present invention, will be described.

[0070] 20 shows an example of a cross-sectional structure of a coin-type electricity storage device (lithium battery) 200 according to an embodiment of the present invention. The electricity storage device 200 includes a disk-shaped positive electrode 212 housed in a metal exterior part 211 and a metal exterior part 212. 2 A disk-shaped negative electrode 214 housed in the exterior part 213 is laminated with a separator 215 interposed therebetween. A metal spring 218 and a spacer 219 are disposed between the exterior part 213 and the negative electrode 214. The interiors of the exterior parts 211 and 213 are filled with a liquid electrolyte, and the peripheries of the exterior parts 211 and 213 are sealed by being crimped with a seal gasket 217 interposed therebetween.

[0071] The positive electrode will now be described. The positive electrode 212 is obtained, for example, by applying a slurry of a metal oxide material, a conductive auxiliary material that aids in electronic conductivity, a binder, and a solvent onto a current collecting metal foil such as rolled aluminum foil to form a coating film, heating and drying to remove the solvent, and then forming the coating into a predetermined dimension and density.

[0072] Metal compound materials that can be used as positive electrode active materials are those that can release electrons to the external circuit of the battery and simultaneously release Li ions to the electrolyte. The amount of Li ions contained varies depending on the chemical composition, crystal structure, etc., but materials that can reversibly release and absorb many Li ions are preferable.

[0073] Examples of such materials include transition metal oxides, composite oxides of lithium and transition metals, and transition metal sulfides. Examples of transition metals include Fe, Co, Ni, and Mn. Specific examples include MnO, V2O5, and V6O 13 Examples of such materials include transition metal oxides such as TiO2, LiNiO2, LiCoO2, LiMn2O4, and inorganic compounds such as TiS2, FeS, and MoS2. In order to improve the properties of these materials, certain elements may be partially substituted with other elements.

[0074] In addition to the above inorganic compounds, there are also organic compounds that can be used as cathode materials. For example, polyaniline, polypyrrole, polyacene, disulfide compounds, polysulfide compounds, N-fluoropyridinium salts, etc. The cathode material can be a mixture of the above inorganic compounds and organic compounds.

[0075] The physical properties of the positive electrode material are determined by the requirements for the battery design and manufacturing process, which are caused by constraints such as the usage form of the power storage device. In the manufacturing of the positive electrode material, the process is designed so that the physical properties can be realized. The physical properties include the powder particle size and distribution, specific surface area, density, etc.

[0076] As an example, the powder particle size is appropriately selected taking into account other constituent requirements of the electricity storage device, but from the viewpoint of improving battery characteristics such as rate characteristics and cycle characteristics, the average particle size is usually preferably 1 to 30 μm, and more preferably 1 to 10 μm.

[0077] Since the above-mentioned positive electrode materials generally have low electronic conductivity, it is preferable to have a conductive assistant that assists electronic conductivity coexist in the positive electrode. The conductive assistant may be a carbon-based material or a metal-based material, or other materials with high electronic conductivity may be used, among which carbon-based materials are preferable.

[0078] The amount of the conductive additive used should be kept to a minimum, while the content of the positive electrode material, which determines the capacity of the electricity storage device, should be maximized.

[0079] Examples of conventional carbon-based materials include soot, acetylene black, ketjen black, lamp black, furnace black, carbon black, graphite, carbon fiber, graphite fiber, nanofiber, nanotube, coke, hard carbon, and amorphous carbon.

[0080] In comparison, the conductive additive of the present embodiment has a significant feature not found in conventional materials, as explained above: the conductive additive of the present embodiment has a nanocarbon-like fine structure, elasticity against stress, and a large specific surface area but a small number of oxygen-containing functional groups. This characteristic makes it possible to maintain the electronic conductivity of the electrode and suppress deterioration of its characteristics even in the electrochemical oxidation environment and stress environment to which the conductive additive is exposed within the battery.

[0081] The suitable ratio of the conductive additive made of the carbon material of this embodiment to be contained in the positive electrode varies depending on the type of positive electrode material, the type and amount of binder, the battery capacity design, etc., but is preferably 0.03 wt % or more in the positive electrode mixture.

[0082] The positive electrode material and the conductive assistant are often in powder form, and in order to fix them together and on the current collecting metal foil, it is preferable to mix them with a small amount of a binder. The binder is required to be chemically and electrochemically inactive and to have some flexibility and affinity, and a plastic resin material is preferably used.

[0083] Examples of the plastic resin material include fluorine-based resins such as polyvinyl fluoride, polyvinylidene fluoride, and polytetrafluoroethylene, CN group-containing polymers such as polyacrylonitrile and polyvinylidene cyanide, polyvinyl alcohol-based polymers such as polyvinyl acetate and polyvinyl alcohol, halogen-containing polymers such as polyvinyl chloride and polyvinylidene chloride, conductive polymers such as polyaniline, alkane-based polymers such as polyethylene, polypropylene, and poly-1,1-dimethylethylene, unsaturated polymers such as polybutadiene and polyisoprene, polymers having rings such as polystyrene, polymethylstyrene, polyvinylpyridine, and poly-N-vinylpyrrolidone, acrylic polymers such as polymethyl methacrylate, polyethyl methacrylate, polybutyl methacrylate, polymethyl acrylate, polyethyl acrylate, polyacrylic acid, polymethacrylic acid, and polyacrylamide, etc. Also, mixtures and modifications of the above resin materials are possible. sex The resin may be a copolymer, derivative, random copolymer, alternating copolymer, graft copolymer, block copolymer, etc. The weight average molecular weight of these resins is usually 10,000 to 3,000,000, and preferably 100,000 to 1,000,000. If the molecular weight is too small, the strength of the coating film decreases, and if it is too large, the viscosity increases, making it difficult to form an electrode.

[0084] In order to distribute the binder sufficiently uniformly and form a coating film of the slurry with a predetermined size, a suitable slurry solvent that dissolves only the binder resin and does not dissolve other materials can be used. For example, when polyvinylidene fluoride is used, dimethylformamide is preferably used as the solvent. Alternatively, N-methylpyrrolidone may be used as the solvent, and it can be appropriately selected and used depending on the conditions of the manufacturing process.

[0085] The current collecting metal foil is preferably made of a material that is inexpensive and can withstand industrial use, and is preferably made of a material that has electrochemical resistance to the potential generated by the positive electrode. Examples of the current collecting metal foil include aluminum foil, nickel foil, titanium foil, and stainless steel foil, and rolled aluminum foil, which is generally available, is more preferable.

[0086] The above-mentioned slurry can be applied to a coating film by a commonly used printing technique. When the coating thickness is small, gravure printing or the like is preferably used, and when the coating thickness is large, doctor blade printing, die printing or the like is preferably used.

[0087] Thereafter, the coating film is dried by heating. Any drying method can be used, and a method that can achieve the desired binding strength by the binder is preferably used.

[0088] Thereafter, when forming the positive electrode into a predetermined size, an industrially available cutting blade and the like and the method thereof are preferably used. In addition, in order to achieve a predetermined density, an industrially available pressing device and the like and the method thereof are preferably used as necessary.

[0089] Next, the negative electrode will be described. The negative electrode 214 is obtained by coating a slurry made of, for example, a carbon-based material, a binder, and a solvent onto a current-collecting metal foil such as rolled copper foil, heating and drying to remove the solvent, and then forming the resulting product into a predetermined size and density.

[0090] As a carbon-based material that can be used for the negative electrode, it is preferable that the material has many stabilization sites inside, and can bond and stabilize Li ions with electrons flowing from an external circuit.

[0091] For example, any material of organic origin can be used regardless of whether it has high or low crystallinity, and graphite, coke, amorphous carbon, hard carbon, polymer carbon, etc. can be suitably used. In this case, the principle is that Li ions are sandwiched between graphene layers, etc., and are stabilized by bonding with electrons.

[0092] As another stabilization mechanism, a method of electrochemically forming an intermetallic compound can also be used, and silicon, tin, zinc, bismuth, antimony, cadmium, lead, germanium, etc. can be suitably used.

[0093] In addition, other materials that have a low electrochemical reaction potential and serve as the negative electrode of the power storage device can also be used, such as compounds of metals and oxygen, sulfur, halogens, nitrogen, phosphorus, etc.

[0094] Depending on the application of the electricity storage device, a plurality of the above negative electrode materials can be mixed in a predetermined ratio and used to obtain a desired discharge profile.

[0095] The physical properties of negative electrode materials are determined by the requirements for device (e.g. storage battery) design and manufacturing process, which are caused by constraints such as the usage form of the electricity storage device. In the manufacturing of materials, the process is designed so that the physical properties can be realized. Physical property values ​​include powder particle size and distribution, specific surface area, density, etc.

[0096] As an example, the powder particle size is appropriately selected taking into account other constituent requirements of the electricity storage device, but from the viewpoint of improving battery characteristics such as rate characteristics and cycle characteristics, the average particle size is usually preferably 1 to 70 μm, and more preferably 3 to 30 μm.

[0097] The above-mentioned negative electrode materials generally have high electronic conductivity, but some materials have a smooth surface and insufficient contact between particles, it is also preferable to use a conductive assistant to assist electronic conductivity. Carbon-based materials, metal-based materials, and other materials with high electronic conductivity can be used as materials, and among them, carbon-based materials are preferable.

[0098] The amount of the conductive additive used should be kept to a minimum, while the content of the negative electrode material, which determines the capacity of the electricity storage device, should be maximized.

[0099] Examples of conventional carbon-based materials include soot, acetylene black, ketjen black, lamp black, furnace black, carbon black, graphite, carbon fiber, graphite fiber, nanofiber, nanotube, coke, hard carbon, and amorphous carbon.

[0100] In comparison, the conductive additive of the present embodiment has a significant feature not found in conventional materials, as described above: it has a nanocarbon-like fine structure, elasticity against stress, and a large specific surface area but a small number of oxygen-containing functional groups.

[0101] Due to this characteristic, Help The agent can maintain the electronic conductivity of the electrode and suppress deterioration of its characteristics even in the electrochemically reducing environment and stress environment to which it is exposed within the battery.

[0102] The preferred ratio of the conductive additive made of the carbon material of this embodiment to be contained in the negative electrode varies depending on the type of negative electrode material, the type and amount of binder, the battery capacity design, etc., but is preferably 0.03 wt% or more per negative electrode mixture.

[0103] The current collecting metal foil is preferably made of a material that is inexpensive and can withstand industrial use, and is preferably made of a material that does not have electrochemical reactivity to the potential generated by the negative electrode. For example, the current collecting metal foil is preferably made of copper foil, nickel foil, titanium foil, or stainless steel foil, and more preferably made of electrolytic copper foil or rolled copper foil, which are generally readily available.

[0104] The method for forming the coating film of the above-mentioned slurry can be a commonly used printing technique. When the thickness dimension is small, gravure printing or the like is preferably used, and when the thickness dimension is large, printing techniques such as doctor blade printing and die printing are preferably used.

[0105] Thereafter, the coating film is dried by heating. Any drying method can be used, and a method that can achieve the desired binding strength by the binder is preferably used.

[0106] Thereafter, when forming the negative electrode into a predetermined size, an industrially available cutting blade and the like and the method are preferably used. In addition, in order to achieve a predetermined density, an industrially available pressing device and the like and the method are preferably used as necessary.

[0107] The negative electrode material and the conductive assistant are often in powder form, and in order to fix them together and on the current collecting metal foil, it is preferable to mix them with a small amount of a binder. The binder is required to be chemically and electrochemically inactive and to have some flexibility and affinity, and a plastic resin material is preferably used.

[0108] Examples of the plastic resin material include fluorine-based resins such as polyvinyl fluoride, polyvinylidene fluoride, and polytetrafluoroethylene, CN group-containing polymers such as polyacrylonitrile and polyvinylidene cyanide, polyvinyl alcohol-based polymers such as polyvinyl acetate and polyvinyl alcohol, halogen-containing polymers such as polyvinyl chloride and polyvinylidene chloride, conductive polymers such as polyaniline, alkane-based polymers such as polyethylene, polypropylene, and poly-1,1-dimethylethylene, unsaturated polymers such as polybutadiene and polyisoprene, polymers having rings such as polystyrene, polymethylstyrene, polyvinylpyridine, and poly-N-vinylpyrrolidone, acrylic polymers such as polymethyl methacrylate, polyethyl methacrylate, polybutyl methacrylate, polymethyl acrylate, polyethyl acrylate, polyacrylic acid, polymethacrylic acid, and polyacrylamide, carboxymethyl cellulose, and styrene butadiene rubber. Also, mixtures and modified versions of the above resin materials may be used. sex The resin may be a copolymer, derivative, random copolymer, alternating copolymer, graft copolymer, block copolymer, etc. The weight average molecular weight of these resins is usually 10,000 to 3,000,000, and preferably 100,000 to 1,000,000. If the molecular weight is too small, the strength of the coating film decreases, and if it is too large, the viscosity increases, making it difficult to form an electrode.

[0109] In order to distribute the binder sufficiently uniformly and form a coating film of the slurry with a predetermined size, a suitable slurry solvent that dissolves only the binder resin and does not dissolve other materials can be used. For example, when polyvinylidene fluoride is used, dimethylformamide is preferably used as the solvent. Alternatively, N-methylpyrrolidone may be used as the solvent, and it can be appropriately selected and used depending on the conditions of the manufacturing process.

[0110] The battery electrolyte of the present invention will now be described.

[0111] An electrolyte is a solute dissolved in an organic solvent, and is usually the main component.

[0112] One of the components of an electrolyte is a solute that is the source of ions, namely a Li salt.

[0113] The type of solute is not particularly limited, and any solute known to be used in the application of the electricity storage device can be used.

[0114] Examples of solutes include inorganic salts such as LiPF6 and LiBF4, fluorine-containing organic Li salts such as LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, Li cyclic 1,2-perfluoroethane disulfonylimide, Li cyclic 1,3-perfluoropropane disulfonylimide, LiN(CF3SO2)(C4F9SO2), LiC(CF3SO2)3, LiPF4(CF3)2, LiPF4(C2F5)2, LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, and LiBF2(C2F5SO2)2, and Li bis(oxalate)borate.

[0115] Among these, LiPF6, LiBF4, LiN(CF3SO2)2 and LiN(C2F5SO2)2 are preferred in terms of exerting battery performance, and LiPF6 and LiBF4 are particularly preferred.

[0116] These Li salts may be used alone or in combination of two or more.

[0117] The content of the Li salt in the electrolyte varies depending on the type of solvent in which the Li salt is dissolved and the mixed composition, but the content of the Li salt in the electrolyte is preferably 7 to 190% by weight, more preferably 10 to 180% by weight, and even more preferably 13 to 150% by weight.

[0118] Next, the organic solvent used in the electrolyte will be described.

[0119] The type of the solvent is not particularly limited, and may be appropriately selected from those conventionally known as solvents. For example, cyclic carbonates, chain carbonates, cyclic ethers, chain ethers, cyclic carboxylates, chain carboxylates, phosphorus-containing organic solvents, etc., each of which does not have an unsaturated bond may be used.

[0120] In addition to viscosity, factors that affect the movement of Li ions include the viscosity and solvation power of the organic solvent. Solvation power is the force that dissociates dissolved ions, and if it is too strong, it will hinder the movement of ions, so there is an optimal value.

[0121] Furthermore, practical electricity storage devices can be used over a wide range of environmental conditions, and physical properties such as the melting point and boiling point of the organic solvent must also fall within certain ranges.

[0122] A practical solution to the above requirements is to use a mixture of multiple organic solvents. The mixture composition is determined by taking into consideration practical properties and combinations of organic solvents with high and low melting points, high and low solvating power, etc.

[0123] In the electrolyte of this embodiment, it is preferable to use a mixture of a cyclic carbonate and a chain carbonate, neither of which has a carbon-carbon unsaturated bond.

[0124] Examples of the cyclic carbonate include alkylene carbonates having an alkylene group having 2 to 4 carbon atoms, such as ethylene carbonate, propylene carbonate, butylene carbonate, etc. Among these, ethylene carbonate and propylene carbonate are preferred from the viewpoint of improving battery characteristics, and ethylene carbonate is particularly preferred.

[0125] As the chain carbonates, dialkyl carbonates are preferred, and the number of carbon atoms in the constituent alkyl groups is preferably 1 to 5, and particularly preferably 1 to 4. Specific examples include dialkyl carbonates such as symmetric chain alkyl carbonates such as dimethyl carbonate, diethyl carbonate, and di-n-propyl carbonate, and asymmetric chain alkyl carbonates such as ethyl methyl carbonate, methyl-n-propyl carbonate, and ethyl-n-propyl carbonate. Among them, dimethyl carbonate is the most preferred in terms of viscosity because it has the lowest viscosity.

[0126] However, since dimethyl carbonate has a rather low boiling point, more suitable properties can be obtained by further mixing it with a chain carbonate having a higher boiling point. Diethyl carbonate is suitable as the chain carbonate to be mixed, but other chain carbonates can also be used without problems.

[0127] The mixing ratio also varies depending on the desired practical properties. There is an optimal composition for the ratio of the chain carbonate to the cyclic carbonate, including the ratio of the Li salt.

[0128] The content of the cyclic carbonate in the electrolyte is preferably 1 to 35% by weight, more preferably 3 to 30% by weight, and even more preferably 4 to 25% by weight. A mixture of multiple cyclic carbonates can be used.

[0129] On the other hand, the content of the chain carbonate in the electrolyte is preferably 40 to 70% by weight, more preferably 43 to 68% by weight. A mixture of multiple chain carbonates can be used.

[0130] As a comprehensive composition, the following combination is preferable. Among the combinations of ethylene carbonate and dialkyl carbonates, ethylene carbonate and dimethyl carbonate are preferred, and may further contain symmetric chain dialkyl carbonate and / or asymmetric chain dialkyl carbonate. For example, those containing ethylene carbonate, symmetric chain dialkyl carbonate and asymmetric chain dialkyl carbonate, such as ethylene carbonate, dimethyl carbonate and diethyl carbonate, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, and ethylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate, are preferred because they have a good balance between cycle characteristics and high-power discharge characteristics. Among them, it is preferred that the asymmetric chain dialkyl carbonate is ethyl methyl carbonate, and the alkyl group of the alkyl carbonate has 1 to 2 carbon atoms.

[0131] Furthermore, as a solvent that aids in the dissociation and movement of ions, cyclic ethers, chain ethers, cyclic carboxylate esters, chain carboxylate esters, etc. may be added in addition to the above-mentioned main organic solvents.

[0132] Examples of cyclic ethers include tetrahydrofuran and 2-methyltetrahydrofuran, and examples of chain ethers include dimethoxyethane and dimethoxymethane.

[0133] Examples of cyclic carboxylates include γ-butyrolactone and γ-valerolactone, and examples of chain carboxylates include methyl acetate, methyl propionate, ethyl propionate, and methyl butyrate.

[0134] Among these, chain carboxylates are particularly preferred.

[0135] Furthermore, it is also preferable that the electrolyte of this embodiment contains a fluorine-containing cyclic carbonate having two or more fluorine atoms.

[0136] The number of fluorine atoms in a fluorine-containing cyclic carbonate having two or more fluorine atoms is not particularly limited, but in the case of fluorinated ethylene carbonate, the lower limit is usually two or more and the upper limit is usually four or less, preferably three or less.

[0137] In the case of fluorinated propylene carbonate, the lower limit is usually 2 or more, and the upper limit is usually 6 or less, preferably 5 or less. In particular, those in which two or more fluorine atoms are bonded to carbons forming a ring structure are preferred from the viewpoint of improving cycle characteristics and storage characteristics.

[0138] Among these, fluorinated ethylene carbonates having two or more fluorine atoms are preferred from the viewpoint of improving battery characteristics, and among these, cis-4,5-difluoro-1,3-dioxolan-2-one, trans-4,5-difluoro-1,3-dioxolan-2-one, and 4,4-difluoro-1,3-dioxolan-2-one are particularly preferred.

[0139] The fluorine-containing cyclic carbonate having two or more fluorine atoms may be used alone or in combination of two or more. The ratio of the fluorine-containing cyclic carbonate compound having two or more fluorine atoms in the non-aqueous electrolyte is not particularly limited in order to exhibit the effects of this embodiment, but is usually 0.001% by weight or more, preferably 0.01% by weight or more, more preferably 0.1% by weight or more, particularly preferably 0.2% by weight or more, and most preferably 0.25% by weight or more. At a concentration lower than this, the effects of this embodiment may be difficult to exhibit. On the other hand, if the concentration is too high, the battery internal pressure may increase during high-temperature storage, so the upper limit is usually 10% by weight or less, preferably 4% by weight or less, more preferably 2% by weight or less, particularly preferably 1% by weight or less, and most preferably 0.5% by weight or less.

[0140] Furthermore, cyclic carbonates having unsaturated bonds and aromatic compounds having a total carbon number of 7 or more and 18 or less may be mixed into the electrolyte.

[0141] Among the cyclic carbonates having unsaturated bonds, vinylene carbonate, vinylethylene carbonate, 4-methyl-4-vinylethylene carbonate, and 4,5-divinylethylene carbonate are preferred from the viewpoint of improving cycle characteristics, and among these, vinylene carbonate and vinylethylene carbonate are more preferred. These may be used alone or in combination of two or more kinds.

[0142] Preferred aromatic compounds having a total carbon number of 7 to 18 include biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, dibenzofuran, and the like.

[0143] It is believed that by suppressing the side reaction between the aromatic compound having a total carbon number of 7 to 18 and the negative and positive electrodes in this way, a significant decrease in discharge characteristics after high-temperature storage can be suppressed.

[0144] In order to achieve the effects of this embodiment, the proportion of aromatic compounds having a total carbon number of 7 to 18 in the electrolyte is usually 0.001% by weight or more, preferably 0.1% by weight or more, particularly preferably 0.3% by weight or more, and most preferably 0.5% by weight or more, and the upper limit is usually 5% by weight or less, preferably 3% by weight or less, and particularly preferably 2% by weight or less. If the concentration is lower than this lower limit, it may be difficult to achieve the effect of improving safety during overcharging. Conversely, if the concentration is too high, battery characteristics such as high-temperature storage characteristics may be reduced.

[0145] The separator 215 separates the positive electrode 212 and the negative electrode 214, prevents a short circuit of current due to contact between the two electrodes, and allows lithium ions to pass through. A porous film made of a resin is preferably used for the separator 215.

[0146] As the form of the membrane, a stretched membrane in which pores are formed by stretching a bulk resin, or a nonwoven fabric in which a large number of fibrous resin fibers are laminated to form a porous structure like a porous membrane, etc. are preferably used.

[0147] Examples of resin materials include polyolefins, and polyethylene is particularly suitable. Polyethylene has a relatively low melting temperature, and when the temperature of the battery rises for some reason (e.g., an unsafe condition such as a short circuit), the pores in the membrane are blocked by thermal melting, preventing the movement of the driving ions, thereby stopping the reaction and ensuring safety.

[0148] The porous membrane formed by the stretching method is usually made by adding a plasticizer to polyolefin and stretching it. Before The plasticizer is later removed, and the areas where the plasticizer was present become the starting points, resulting in a relatively uniform microporous structure.

[0149] In producing a stretched film, stretching is usually performed in both the longitudinal and transverse directions. In addition to the removal of the plasticizer, etc., any atmosphere, temperature, speed, stress, number of process repetitions, etc. can be appropriately combined to obtain a suitable stretched film.

[0150] Although the above manufacturing process can produce a high-quality stretched membrane, it is a multi-step process, which makes it difficult to reduce manufacturing costs such as process costs, and may be a negative factor in the widespread use of electricity storage devices.

[0151] On the other hand, by simplifying the process so that the stretching is performed only in the longitudinal direction without using plasticizers, it is possible to obtain a porous membrane that can be manufactured on an industrial level and can reduce the manufacturing cost. In this case, the applicable resin is polyolefin, and polypropylene is preferably used.

[0152] The separator interposed between the positive electrode and the negative electrode may be formed from an electrically insulating porous body. For example, a polymer film or a fiber nonwoven fabric made of polyolefin such as polyethylene or polypropylene, polyester, polyethylene terephthalate, or polyimide can be used as the separator. The separator may be made of one material alone or a plurality of materials. The separator may be a single layer or a multilayer (composite film). The separator may contain inorganic material nanoparticles such as ceramic. The separator may be used by coating both sides with a polymer compound such as polyvinylidene fluoride.

[0153] In the nonaqueous electrolyte battery according to the present embodiment, a gelled electrolyte may be used by including a polymer compound that swells with an organic solvent to serve as a support for holding the nonaqueous electrolyte. By including a polymer compound that swells with an organic solvent, high ionic conductivity can be obtained, excellent charge / discharge efficiency can be obtained, and leakage of the battery can be prevented. When the nonaqueous electrolyte includes a polymer compound, the content of the polymer compound is preferably within a range of 0.1% by mass to 10% by mass of the nonaqueous electrolyte.

[0154] In addition, when a polymer compound such as polyvinylidene fluoride is applied to both sides of the separator, the mass ratio of the non-aqueous electrolyte to the polymer compound is preferably within a range of 50: 1 to 10: 1. By keeping the ratio within this range, higher charge / discharge efficiency can be obtained.

[0155] Examples of the polymeric compound include ether-based polymeric compounds such as polyvinyl formal, polyethylene oxide, and crosslinked products containing polyethylene oxide, ester-based polymeric compounds such as polymethacrylate, acrylate-based polymeric compounds, and vinylidene fluoride polymers such as polyvinylidene fluoride and copolymers of vinylidene fluoride and hexafluoropropylene. The polymeric compound may be used alone or in combination. In particular, from the viewpoint of the swelling prevention effect during high-temperature storage, it is desirable to use a fluorine-based polymeric compound such as polyvinylidene fluoride.

[0156] The electricity storage device having the above-mentioned configuration operates as follows. When the power storage device is charged, Li ions contained in the positive electrode 212 pass through the separator 215 and are inserted between the layers of the layered structure of graphite contained in the negative electrode 214. When the power storage device is subsequently discharged, the Li ions are released from between the layers of the layered structure contained in the negative electrode 214 and pass through the separator 215 back to the positive electrode 212.

[0157] Although one embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims.

[0158] In the above embodiment, a coin-type lithium ion battery has been described as an example of the power storage device, but the power storage device of this embodiment can be similarly applied to devices having other shapes such as a button type, a paper type, a square type, or a cylindrical type having a spiral structure. Also, the power storage device of this embodiment can be made in various sizes such as a thin type or a large type.

[0159] Furthermore, in the above description, an embodiment is described assuming a case where the electricity storage device has a liquid electrolyte as the electrolyte according to this embodiment, but any other electrolyte can be applied, and by way of example, a gel electrolyte or a solid electrolyte can also be suitably used. EXAMPLES

[0160] Examples of the present embodiment will be described below. The present invention is not limited to the following examples. First, examples of the carbon material according to the present embodiment will be described.

[0161] [Example 1] (template) First, alumina nanoparticles (TM-100, manufactured by Taimei Chemical Industry Co., Ltd.) were prepared as nanoparticles for the template. The BET specific surface area of ​​the alumina nanoparticles was determined as S [m 2 / g], and the density of alumina is ρ [g / m 3 ], the formula d0[nm]=6 / (S BET ×ρ)×10 9 The average particle size d0 of the alumina nanoparticles was calculated by the above method, and the average particle size d0 of the alumina nanoparticles was found to be 14 nm.

[0162] (Coating process) In the coating process, methane was used as the source gas and argon was used as the process gas, and chemical vapor deposition was carried out at 900°C for 2 hours. After that, the flow rate of methane gas was set to 0 ml / min, and the substrate was held at this temperature for 30 minutes, and then naturally cooled to room temperature.

[0163] (separation process) Next, the molded product obtained by the coating process and hydrofluoric acid were mixed in a beaker and stirred at room temperature for 2 hours. The molded product separated from the mold was then taken out, and the sample was washed five times with pure water while being filtered using a membrane filter (0.1 μm), and then suction filtered. After that, the molded product and hydrofluoric acid were mixed and stirred again, and the molded product was suction filtered using pure water, in the same manner as above.

[0164] Next, the molded product was placed in a screw cap bottle containing acetone, the cap was closed, and the bottle was shaken well. Then, the molded product was left to stand overnight at 60°C in a thermostatic oven. The next day, the supernatant was discarded, and fresh acetone was added, and the bottle was left to stand at 60°C. Warm and dryThe mixture was then left to stand in a thermostatic oven at 60°C for 3 hours. The supernatant was then discarded, and new acetone was added, and the mixture was left to stand in a thermostatic oven at 60°C for 3 hours again. The acetone was then removed by suction filtration, and the mixture was dried twice in a thermostatic oven at 150°C for 10 hours under reduced pressure of 1000 Pa or less to produce a carbon meso sponge (CMS) as a molded product.

[0165] (Stabilization process) Next, the CMS was placed in the sample chamber of a high-temperature heating furnace (IZU-SMS005, manufactured by Izumi Tech Co., Ltd.), the sample chamber was evacuated, and the temperature was then raised to 1800°C at a heating rate of 15°C / min with argon gas flowing at 10 ml / min. The CMS was sintered by heat treatment at 1800°C for 1 hour, and GMS (graphene meso sponge) was produced as a carbon material.

[0166] [Example 2] A carbon material was produced in the same manner as in Example 1, except that alumina nanoparticles (TM-300, manufactured by Taimei Chemical Industry Co., Ltd.) were used as nanoparticles for the template, and the heat treatment temperature in the stabilization step was changed to 1600° C. The average particle size of the alumina nanoparticles was measured in the same manner as in Example 1, and was found to be 7 nm.

[0167] [Example 3] A carbon material was produced in the same manner as in Example 1, except that alumina nanoparticles (TM-300, manufactured by Taimei Chemical Industry Co., Ltd.) were used as nanoparticles for the template. The alumina nanoparticles used in Example 3 were the same as those used in Example 2.

[0168] [Example 4] A carbon material was produced in the same manner as in Example 1, except that alumina nanoparticles (product name: SBa-200, manufactured by Sasol Chemical) were used as nanoparticles for the template. The average particle size of the alumina nanoparticles was measured in the same manner as in Example 1, and was found to be 8 nm.

[0169] [ Reference example 1 ] A carbon material was produced in the same manner as in Example 1, except that magnesium oxide nanoparticles (manufactured by US Research Nanomaterials, product number: Magnesium Oxide MgO Nanopowder / Nanoparticles (MgO, 99+%, 20 nm)) were used as nanoparticles for the template, the conditions for the coating process were changed, and hydrochloric acid was used instead of hydrofluoric acid in the separation process. The average particle size of the magnesium oxide nanoparticles was measured in the same manner as in Example 1 and was found to be 30 nm.

[0170] Reference example 1 In the coating process, the flow rates of methane gas and argon gas were changed to adjust the coating amount. Also, the treatment time under the condition of 900° C. was changed to 50 minutes. The other conditions in the coating process were the same as in Example 1.

[0171] [Comparative Example 1] In Comparative Example 1, zeolite-templated carbon (ZTC) was produced as a carbon material by the following method. First, in a round-bottom flask depressurized using a vacuum pump, 15 g of Y-type zeolite (HZS-320NAA, manufactured by Tosoh Corporation) was dried overnight in a heated environment at 150°C, and then impregnated with furfuryl alcohol (FA) to obtain a FA / zeolite composite. Next, the FA / zeolite composite was placed in a quartz reaction tube and heat-treated at 80°C for 24 hours under N2 flow, and then held at 150°C for 8 hours to obtain a polyfurfuryl alcohol (PFA) / zeolite composite.

[0172] Next, the PFA / zeolite composite was used as a template to coat a carbon layer. Specifically, 15 g of the PFA / zeolite composite was placed in a horizontal CVD apparatus, and the PFA / zeolite composite was coated with a carbon layer by chemical vapor deposition, in which the maximum temperature was kept at 700°C for 2 hours under a flow of N2 containing 4 vol% propane. Next, the introduction of propane gas was stopped, and heat treatment was performed at 900°C for 3 hours under a flow of N2, to obtain a zeolite / carbon composite. Next, the zeolite / carbon composite was treated with hydrofluoric acid (HF) to remove the zeolite template, thereby obtaining ZTC.

[0173] [Comparative Example 2] ZTC was prepared as a carbon material in the same manner as in Comparative Example 1, except that the preparation conditions for the zeolite / carbon composite were changed.

[0174] In Comparative Example 2, first, 15 g of the Y-type zeolite used in Comparative Example 1 was dried overnight at 150°C under vacuum. Then, the Y-type zeolite was used as a template and placed in a rotary kiln-type CVD apparatus, and chemical vapor deposition was performed at a maximum temperature of 600°C for 4 hours in an argon gas flow section containing 15 vol% acetylene, to cover the template with a carbon layer. Next, the introduction of acetylene gas was stopped, and heat treatment was performed at 900°C for 3 hours under N2 flow as in Comparative Example 1, to obtain a zeolite / carbon composite with a stabilized carbon skeleton structure. Next, the template was removed in the same manner as in Comparative Example 1 to obtain ZTC.

[0175] [Comparative Example 3] ZTC was prepared as a carbon material in the same manner as in Comparative Example 1, except that the preparation conditions for the zeolite / carbon composite were changed.

[0176] In Comparative Example 3, 0.5 g of X-type zeolite (Molecular Sieve 13X powder, manufactured by Union Showa Co., Ltd.) was first vacuum-dried at 150°C for 6 hours. Then, 0.5 g of the X-type zeolite was used as a template and placed in a quartz reaction tube, and chemical vapor deposition was performed at 600°C for 4 hours under a flow of N2 containing 15 vol% acetylene to cover the template with a carbon layer. Next, the introduction of acetylene gas was stopped, and heat treatment was performed at 850°C for 3 hours to obtain a zeolite / carbon composite with a stabilized carbon skeleton structure. Next, the template was removed in the same manner as in Comparative Example 1 to obtain ZTC.

[0177] [Comparative Example 4] A molded product, which is CMS, a precursor of GMS, was obtained in the same manner as in Example 1, except that the stabilization step was not carried out.

[0178] [Comparative Example 5] A molded product, which is CMS, a precursor of GMS, was obtained in the same manner as in Examples 2 and 3, except that the stabilization step was not performed.

[0179] [Comparative Example 6] A molded product, which is CMS, a precursor of GMS, was obtained in the same manner as in Example 4, except that the stabilization step was not performed.

[0180] [Comparative Example 7] A molded product, which is CMS, a precursor of GMS, was obtained in the same manner as in Comparative Example 6, except that the following hot pressing step was performed. First, a molded product was produced in which a carbon layer was coated on a mold in the same manner as in Comparative Example 6. The molded product was then placed in a mold and placed in a hot press device (AG-50kNXDp, manufactured by Shimadzu Corporation). Pressure was then applied at room temperature and under vacuum at a sliding speed of 0.01 mm / sec, and heating was started when the temperature reached 30 MPa. When the temperature reached 600°C, the pressure and temperature were maintained for 3 hours, and the molded product was removed after being sufficiently cooled. The mold was then removed in the same manner as in Comparative Example 6 to obtain a molded product that was CMS, a precursor of GMS.

[0181] [Comparative Example 8] A molded product, which is CMS, a precursor of GMS, was obtained in the same manner as in Comparative Example 6, except that the conditions of the coating step were changed. In the coating process of Comparative Example 8, first, alumina nanoparticles were circulated in acetonitrile solvent with argon at a flow rate of 225 ml / min, and chemical vapor deposition was performed for 200 minutes under the condition of 650 ° C., and the carbon layer of the graphene skeleton doped with nitrogen was coated on the template to obtain a molded product. Next, the molded product was heat-treated at 1800 ° C. for 1 hour, and then naturally cooled to room temperature. CMS, a precursor of GMS, was produced.

[0182] [Comparative Example 9] As Comparative Example 9, single-walled carbon nanotubes (SWCNTs) (manufactured by Zeon Corporation, product number: SG101) were prepared.

[0183] [Comparative Example 10] Activated carbon (MSC-30, manufactured by Kansai Thermochemical Co., Ltd.) was prepared as Comparative Example 10. MSC-30 was synthesized by alkali activation of petroleum coke.

[0184] [Comparative Example 11] Activated carbon (Shirasagi-P, manufactured by Osaka Gas Chemicals Co., Ltd.) was prepared as Comparative Example 11. Shirasagi-P was synthesized by activating wood with water vapor.

[0185] [Characteristics evaluation] Example 1 4, Reference example 1 The carbon materials of Comparative Examples 1 to 11 were subjected to characteristic evaluation by the following means.

[0186] (Bulk modulus K_measured by mercury intrusion method) First, a sample was placed in a vacuum vessel, mercury was introduced, and an isotropic pressure was applied to the sample in the range of 3 KPa to 400 MPa, and a correlation curve was obtained between the volume change ΔV of the mercury contained in the vacuum vessel and the pressure P. Under low pressure conditions, the volume of mercury decreases rapidly due to the impregnation of the spaces between the particles, and ΔV decreases rapidly. From this result and the initial volume V0 of the sample, a correlation curve between the volume change rate ΔV / V0 and the pressure P was plotted. Figures 5A to 5E show the results of Examples 1 to 5. 4 and Reference Example 1 6A to 6C are graphs showing the results of mercury intrusion measurement for Comparative Examples 1 to 3, Figures 7A to 7E are graphs showing the results of mercury intrusion measurement for Comparative Examples 4 to 8, and Figures 8A to 8C are graphs showing the results of mercury intrusion measurement for Comparative Examples 9 to 11. The bulk modulus K was defined using a range of the measured graphs that had a good linear positive value, where no aggregation of primary particles or intrusion of mercury into pores was observed.

[0187] In mercury intrusion measurements, the range where a sudden change in volume occurs is thought to be where aggregation of primary particles and intrusion of mercury into pores occur, and it is therefore preferable to use a range with little linearity where no sudden change in volume occurs for calculations. Therefore, when calculating the bulk modulus based on the results of mercury intrusion measurements, the stress-strain curve was taken to be the range where only compression of the sample occurs, excluding the range where mercury penetrates between the particles and into the pores of the sample (thick line in the figure). The bulk modulus K was calculated from the stress-strain curve using the following formula (4). In the formula, V0 is the volume of mercury at a certain mercury pressure P, ΔV is the volume change when the mercury pressure increases by ΔP, and is a negative value. K = -V0(ΔP / ΔV) (4)

[0188] The measurement results are shown in FIGS. 5A to 5E. 4 and Reference Example 1 are both examples in which GMS was produced and measured, and since GMS is a mesoporous body, the pressure range in which mercury penetrates into the pores is relatively small. The same is true for CMS shown in Figs. 7A to 7E. On the other hand, ZTC shown in Figs. 6A to 6C is a micropolynomial, and therefore the pressure range in which mercury penetrates into the pores is relatively wide. Moreover, in Example 1, the results of which are shown in Fig. 5A, and Comparative Example 4, the results of which are shown in Fig. 7A, no behavior of mercury penetrating between particles is observed, and the change in the volume change rate with respect to pressure is a gradual 5.0 × 10 -5 GPa~5.0×10 -3 The region around GPa was used to calculate the bulk modulus. In Comparative Example 9, whose measurement results are shown in FIG. 8A, the behavior of mercury penetrating into the tube was not confirmed, so the region to be used as the pressure-strain curve was determined based on the inner diameter of the SWCNT observed by TEM. In Comparative Example 10, whose measurement results are shown in FIG. 8B, a sudden change in volume occurs in the region of 0.0001 to 0.01 GPa, 0.1 GPa or more. In Comparative Example 11, whose measurement results are shown in FIG. 8C, the pore diameter is small, so mercury does not penetrate into the pores, and from the pore diameter distribution, a pressure of 2.4×10 -2 ~1.3×10 -1 GPa was used for the calculations.

[0189] (Evaluation of the average graphene network size L_edge site amount measurement) Next, Examples 1 to 4 and 6. Reference example 1, For Comparative Examples 4 to 8, the average graphene mesh plane size L was calculated using the coronene model. The average graphene mesh plane size L is the size of one graphene sheet constituting the carbon material, and is calculated using the following formula (5). In the formula, N edge is the average amount of edge sites in the carbon material, and a0 is the lattice constant (0.2461 nm) of the carbon material in the a-axis direction. L=(a0 / N edge ) · · · (5)

[0190] Average amount of edge sites in carbon material N edge was measured by the temperature programmed desorption (TPD) method using an ultra-high sensitivity vacuum TPD instrument (developed at Tohoku University, see T. Ishii et al., CARBON, 80, 2014, 135-145). FIG. 9 is a diagram illustrating an ultra-high sensitivity vacuum TPD instrument 60 used in the temperature programmed desorption analysis. The ultra-high sensitivity vacuum TPD instrument 60 includes a quartz reactor including a radioactive thermometer 41, a sample holder 42, and a high-frequency induction coil 43, and a detection unit connected to the quartz reactor. The detection unit includes, for example, a gas reservoir, a turbo molecular pump TMP, a rotary pump RP, a cold cathode Pirani gauge P1, and a capacitance gauge P2. Specifically, according to the method described in the above literature, first, about 1 mg of sample is placed on the sample holder, and about 1.0×10 -5 The sample was heated to 1800°C at a heating rate of 10°C / min under a high vacuum of 100 Pa, and the gases desorbed from the sample were quantified using a mass spectrometer. The desorbed gases were quantified by quantifying H2, H2O, CO, and CO2. The measurement data was corrected using blank data obtained by measuring only the sample stage.

[0191] 10A to 10E are diagrams showing examples 1 to 4 and Reference Example 111A to 11C show the gas emission patterns of Comparative Examples 1 to 3, FIGS. 12A to 12E show the gas emission patterns of Comparative Examples 4 to 8, and FIGS. 13A to 13C show the gas emission patterns of Comparative Examples 9 to 11.

[0192] Edge site amount N edge [μmol / g] was quantified using the following formula (6): H2、 N H2O 、 N CO , N CO2 are the amounts of desorbed hydrogen, water, carbon monoxide, and carbon dioxide, respectively, measured by the TPD method. N edge =2 N H2 +2·N H2O +N CO ++N CO2 (6)

[0193] [Edge site specific surface area S edge Measurement of Furthermore, the above edge site amount N edge Using the above, from the following formula (7), Examples 1 to 4, Reference example 1 , and the edge site specific surface area S of Comparative Examples 1 to 11 edge was calculated. In the formula, N edge is the amount of edge sites in the carbon material, and A edge is the specific surface area per edge site, and N A is the Avogadro constant. edge is the average area geometrically calculated from the crystal structure of graphite, and is 0.083 nm 2 We took advantage of the fact that S edge =N edge ×A edge ×N A (7)

[0194] Doped nitrogen is classified into pyrrole type, pyridine type, and quaternary nitrogen. Doped nitrogen is released as N2, HCN, and NH3, but among the above classifications, quaternary nitrogen, which is nitrogen within the graphene network plane, is released as N2 at 900°C or higher. Therefore, the nitrogen content N within the graphene network plane was calculated by quantifying N2 at 900°C or higher based on the following formula (8). In the formula, N N2 (>900℃) means the amount of N2 desorbed at 900℃ or higher. N=N N2 (>900℃)×10 -6 ×28.0×100···(8)

[0195] [Average number of layers n_nitrogen adsorption / desorption measurement] Example 1 to Example 4, Reference example 1 The carbon materials of Comparative Example 1 to Comparative Example 11 were subjected to nitrogen adsorption / desorption measurements to determine the BET specific surface area S of the carbon materials. Next, the BET specific surface area S and the edge site specific surface area S of the carbon materials were edge The theoretical specific surface area of ​​graphene S graphene The average number of layers n of the carbon material was calculated by calculating the ratio of these values ​​using the above formula (1). The theoretical specific surface area of ​​graphene S graphene is 2627m 2 The BET specific surface area S of the carbon material was as was calculated by the following nitrogen adsorption / desorption measurement. Here, the BET specific surface area S of the carbon material was determined by the BET method.

[0196] The nitrogen adsorption and desorption measurements were carried out at -196°C using a specific surface area and pore distribution measuring device (BELSORP max, manufactured by BEL Japan). Before the measurements, a degassing treatment was carried out by vacuum drying at 150°C for 6 hours. The equilibrium judgment condition for measuring the pressure inside the sample tube was 300 seconds. FIG. 14A shows the results of Examples 1 to 3. 4 and Reference Example 114A to 14E are graphs showing nitrogen adsorption and desorption isotherms for Comparative Examples 1 to 3, FIG. 14B is a graph showing nitrogen adsorption and desorption isotherms for Comparative Examples 4 to 8, FIG. 14D is a graph showing nitrogen adsorption and desorption isotherms for Comparative Examples 9, and FIG. 14E is a graph showing nitrogen adsorption and desorption isotherms for Comparative Examples 10 and 11. In FIG. 14A to FIG. 14E, graphs with filled circles represent nitrogen adsorption isotherms, and graphs with unfilled circles represent nitrogen desorption isotherms.

[0197] [Pore volume Vtotal] Based on the nitrogen adsorption / desorption isotherm, the amount of nitrogen adsorbed at -196°C and a relative pressure of P / P0 = 0.96 was converted to the volume of liquid nitrogen density to obtain the pore volume V total was measured.

[0198] [Pore size distribution] Adsorption isotherms are roughly classified into two types, I type and IV type. Figures 15A and 15B are schematic diagrams for explaining the general shape of the adsorption isotherm, with Figure 15A showing a schematic diagram of the I type adsorption isotherm and Figure 15B showing a schematic diagram of the IV type adsorption isotherm. Next, for samples showing the I type adsorption isotherm, the pore size distribution was analyzed with reference to a kernel calculated by density functional theory (DFT method) assuming slit-type pores using the software Autosorb 1 for the adsorption isotherm. Next, for samples showing the IV type adsorption isotherm, the pore size distribution was analyzed by applying the Barrett-Joyner-Halenda method (BJH method) to each adsorption isotherm. Figure 16A shows the results of Examples 1 to 4. 4 and Reference Example 1 16B is the pore size distribution of Comparative Examples 1 to 3, FIG 16C is the pore size distribution of Comparative Examples 4 to 8, FIG 16D is the pore size distribution of Comparative Example 10, and FIG 16E is the pore size distribution of Comparative Examples 10 and 11. The pore size distribution was fitted with a Gaussian function to calculate the pore size d of the carbon material.

[0199] [Surface torsion t] Example 1 to Example 4, Reference example 1For the samples of Comparative Examples 4 to 8, the surface torsion t was calculated from the following formula (3) using the pore diameter d and the average particle diameter d0 of the template nanoparticles. For Comparative Example 7, the surface torsion t was calculated before the hot pressing process.

[0200] t=4πr0 2 / 4πr 2 =d0 2 / d 2 (3)

[0201] Example 1 to Example 4, Reference example 1 The properties of the carbon materials of Comparative Examples 1 to 11 are summarized in Table 1.

[0202] [Table 1]

[0203] It was confirmed that the surface twist t of Examples 1 to 5 and Comparative Examples 4 to 8 is influenced by the average particle size d0 and the average number of layers n of the template nanoparticles, and increases as the average particle size d0 increases and the average number of layers n decreases. This is thought to be because those having the structural characteristics described above are susceptible to the effects of capillary shrinkage when the template is removed in the separation process. The same template was used in Example 1 and Comparative Example 4, Examples 2 and 3 and Comparative Example 5, and Example 4 and Comparative Examples 6 to 8, and the Example (GMS) and Comparative Example (CMS) using the same template. of In comparison, the example having a larger graphene network size L exhibits a larger bulk modulus K, and the larger the graphene network size L, the smaller the edge site amount N edge The resulting structure is continuous with minimal wear and tear, providing durable structural properties.

[0204] In carbon materials, the larger the pore diameter d, the smaller the curvature of the graphene sheet. Also, the larger the surface torsion t, the more distorted the carbon material will be, making it more difficult to apply force uniformly and more likely to deform. Therefore, it is believed that the larger the pore diameter d and the larger the surface torsion t, the higher the mechanical flexibility will be and the smaller the bulk modulus K will be.

[0205] Comparing Comparative Example 6 and Comparative Example 8, Comparative Example 8, which has a high nitrogen doping concentration, has a large bulk modulus K and a large amount of nitrogen in the graphene network plane. of It was confirmed that carbon materials with a higher doping concentration are harder, which is believed to be because the carbon-nitrogen double bond energy is higher than the carbon-carbon double bond energy, making it easier to maintain the planar network of six-membered rings that ensures planarity.

[0206] FIG. 17 shows Examples 1 to 4. 4, Reference example 1 17 is a graph showing the relationship between the bulk modulus K and structural characteristics of Comparative Examples 1 to 11. In Fig. 17, the vertical axis shows the bulk modulus K measured by mercury intrusion porosimetry, and the horizontal axis shows the structural characteristics of the carbon material represented by the following formula (9). In Fig. 17, the indexes are optimized by the least squares method so as to obtain the bulk modulus and the linear diameter relationship of the following formula (9). (L 0.8 ·n 0.8 N 0.8 ) / (d 0.5 t 5.9 ) · · · (9) As shown in Fig. 17, the bulk modulus K of a carbon material is proportional to the structural characteristics of the carbon material as shown in the above formula (9). That is, the bulk modulus K is approximated by the following formula (10), where α is a proportionality constant, and in the graph shown in Fig. 17, α = 0.16.

[0207] K = α × (L 0.8 ·n 0.8 N 0.8 ) / (d 0.5 t 5.9 ) · · · (10)

[0208] Therefore, based on this proportional relationship, it is effective to adjust the manufacturing conditions in advance or during the preparation of the carbon material as an adjustment step so that the carbon material has the desired structural characteristics. Note that the proportional relationship is not limited to the carbon materials of the examples, but also applies to the carbon materials of the comparative examples, and it is effective to adjust the manufacturing conditions based on the above formula (10) so that, for example, activated carbon, SWCNT, ZTC, and CMS have the desired structural characteristics.

[0209] [SEM observation] 18A, 18B, 18C, and 18D are SEM images of Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4, respectively. In Example 1 and Comparative Example 4, which have small surface twist t, the surface twist t is not so large that wrinkles due to shape distortion were not observed, but in experimental data (not shown) for those with large surface twist t, wrinkles due to shape distortion may be observed.

[0210] [Raman spectroscopy] Example 1 to Example 4 and Reference Example 1 The Raman spectrum of the carbon material was measured using a micro-Raman microscope (LabRAM HR-800, manufactured by Horiba, Ltd.). The measurement was performed using a 532 nm laser with a filter set to D1 and a hole set to 100 μm. The measurement range was 300 to 3500 cm. -1 FIG. 19 shows the results of Examples 1 to 3. 4 and Reference Example 1 The horizontal axis in Fig. 17 represents the Raman shift (cm -1 19, the graphs in order from lowest intensity are Example 1, Example 2, Example 3, Reference example 1 1 is a graph of Example 4.

[0211] Example 1 to Example 4 and Reference Example 1In all of the above, the presence of the D band, D' band, G band, and 2D band due to secondary phonon scattering, which are derived from defects such as non-hexagonal sites including edge sites, and the skeletal vibration of the graphene sheet, was confirmed. The D band appears as a hexagonal breathing mode at the point where the hexagonal symmetry of the graphene network plane is broken. Example 1 to Example 4 and Reference Example 1 The peaks in the Raman spectrum are given by the Raman shift (cm -1 The peaks of the D band, G band, D' band, and 2D band are in ascending order of magnitude. The D' band is a hexagonal deformation mode, and is forbidden in an infinitely large hexagonal mesh surface. Therefore, it can be seen from the Raman spectra of Examples 1 to 5 that the D' band is a hexagonal deformation mode and is forbidden in an infinitely large hexagonal mesh surface. 4 and Reference Example 1 It was confirmed that the carbon material also had a graphene skeleton. 4 and Reference Example 1 In all of the above, the 2D peak is located on the lower layer side compared to the 2D peak of HOPG, and can be fitted with a single Lorentzian function. 4 and Reference Example 1 Single-layer graphene was grown.

[0212] Next, an example of the power storage device according to this embodiment, specifically, an example of a coin-type lithium battery, which is one example of the power storage device, will be described.

[0213] [Example 6] <Preparation of positive electrode> A positive electrode paste was prepared by mixing 93% by weight of lithium cobalt oxide (LiCoO2) powder with an average particle size of 3 μm, 2% by weight of acetylene black as a conductive additive, and 5% by weight of PVdF in N-methyl-pyrrolidone (NMP) as a solvent until homogeneous. The obtained paste was applied to an aluminum foil with a thickness of 20 μm and dried. This was punched out to a diameter of 14 mm and pressed to obtain a positive electrode.

[0214] <Preparation of negative electrode> 97% by weight of artificial graphite, 1% by weight of the carbon material of Example 1 as a conductive assistant, 1% by weight of carboxymethyl cellulose, and 1% by weight of styrene butadiene rubber (SBR) were mixed homogeneously using distilled water as a solvent to prepare a negative electrode paste. The obtained paste was applied to a copper foil having a thickness of 20 μm and dried. This was punched out to a diameter of 15 mm and pressed to obtain a negative electrode.

[0215] <Preparation of non-aqueous electrolyte> Lithium hexafluorophosphate (LiPF6) was added to a mixed solvent prepared by adjusting the volume ratio of ethylene carbonate (EC) and dimethyl carbonate (DMC) to 3:7, and dissolved therein so that the electrolyte concentration was 13% by weight, to obtain an electrolyte solution.

[0216] <Coin cell battery assembly> A uniaxially stretched microporous polypropylene membrane was sandwiched between the above-mentioned positive and negative electrodes, a specified amount of the above-mentioned electrolyte was added, and the membrane was housed in the exterior parts of a 2032-type coin battery (height 3.2 mm, diameter 20 mm) together with a metal spring and spacer, and then sealed by crimping a seal gasket to produce a coin battery.

[0217] [Example 7] A coin battery was produced in the same manner as in Example 6, except that the carbon material of Example 3 was used as the conductive assistant for the negative electrode.

[0218] [Example 8] A coin-type battery was fabricated in the same manner as in Example 6, except that a positive electrode was made using 94% by weight of lithium cobalt oxide (LiCoO2) powder having an average particle size of 3 μm, 1% by weight of the carbon material of Example 1 described above as a conductive additive, and 5% by weight of PVdF, and a negative electrode was made using 1% by weight of acetylene black as a conductive additive.

[0219] [Example 9] A coin-type battery was produced in the same manner as in Example 8, except that the carbon material of Example 1 was used as the positive electrode conductive assistant and the negative electrode conductive assistant, respectively.

[0220] [Example 10] A coin-type battery was fabricated in the same manner as in Example 9, except that the positive electrode contained 94.5% by weight of lithium cobalt oxide (LiCoO2) powder and 0.5% by weight of the carbon material of Example 1 as the positive electrode conductive assistant.

[0221] [Example 11] A coin-type battery was fabricated in the same manner as in Example 9, except that 94.8 wt % of lithium cobalt oxide (LiCoO2) powder was used for the positive electrode, and 0.2 wt % of the carbon material of Example 1 was used as the positive electrode conductive assistant.

[0222] [Example 12] A coin-type battery was produced in the same manner as in Example 9, except that 97.4% by weight of artificial graphite was used for the negative electrode, and 0.6% by weight of the carbon material of Example 1 was used as the negative electrode conductive assistant.

[0223] [Example 13] A coin-type battery was produced in the same manner as in Example 9, except that 97.9% by weight of artificial graphite was used for the negative electrode, and 0.1% by weight of the carbon material of Example 1 was used as the negative electrode conductive assistant.

[0224] [Example 14] A coin-type battery was produced in the same manner as in Example 9, except that 97.97% by weight of artificial graphite was used for the negative electrode, and 0.03% by weight of the carbon material of Example 1 was used as the negative electrode conductive assistant.

[0225] [Comparative Example 12] A coin-type battery was produced in the same manner as in Example 6, except that acetylene black was used as the conductive assistant for the negative electrode.

[0226] [Comparative Example 13] A coin-type battery was produced in the same manner as in Example 6, except that the carbon material of Comparative Example 1 was used as the conductive assistant for the negative electrode.

[0227] [Comparative Example 14] A coin-type battery was produced in the same manner as in Example 6, except that the carbon material of Comparative Example 9 was used as the conductive assistant for the negative electrode.

[0228] [Comparative Example 15] A coin-type battery was produced in the same manner as in Example 9, except that the carbon material of Comparative Example 1 was used as the conductive assistant for the positive and negative electrodes.

[0229] [Comparative Example 16] A coin-type battery was fabricated in the same manner as in Comparative Example 12, except that for the positive electrode, 93.5% by weight of lithium cobalt oxide (LiCoO2) powder and 1.5% by weight of acetylene black were used as a positive electrode conductive assistant.

[0230] [Comparative Example 17] A coin-type battery was fabricated in the same manner as in Comparative Example 12, except that for the positive electrode, 94.5% by weight of lithium cobalt oxide (LiCoO2) powder and 0.5% by weight of acetylene black were used as a positive electrode conductive assistant.

[0231] [Comparative Example 18] A coin-type battery was fabricated in the same manner as in Comparative Example 12, except that for the positive electrode, 94.8% by weight of lithium cobalt oxide (LiCoO2) powder and 0.2% by weight of acetylene black were used as a positive electrode conductive assistant.

[0232] [Comparative Example 19] A coin-type battery was produced in the same manner as in Example 12, except that 0.6% by weight of acetylene black was used as a negative electrode conductive assistant.

[0233] [Comparative Example 20] A coin-type battery was produced in the same manner as in Example 12, except that 97.9% by weight of artificial graphite and 0.1% by weight of acetylene black were used as a negative electrode conductive assistant.

[0234] [Comparative Example 21] A coin-type battery was produced in the same manner as in Example 12, except that 97.97% by weight of artificial graphite and 0.03% by weight of acetylene black were used as a negative electrode conductive additive in the negative electrode.

[0235] The coin type batteries prepared in Examples 6 to 14 and Comparative Examples 12 to 21 were charged to 4.35 V at a constant current of 2.0 mA at 0° C., and then discharged to 3.0 V at a constant current of 2.0 mA at 0° C. After that, the charge and discharge were repeated 10 times in the same manner, and the retention rate of the discharge capacity was measured. The results are shown in Table 2.

[0236] [Table 2]

[0237] When the carbon material of this embodiment was used as a conductive additive in the positive electrode, the cycle characteristics of the battery were improved, even though the test was conducted at a low temperature. This is presumably because the overvoltage during charging was low, and lithium was not desorbed in an amount greater than the design standard, so the burden on the negative electrode was small.

[0238] In addition, when the carbon material of this embodiment was used as a conductive assistant for the negative electrode, the initial loss capacity of the negative electrode was smaller, the initial efficiency was improved, and the initial discharge capacity was higher than in the comparative example. Although the test was conducted at a low temperature, the cycle characteristics of the battery were improved. This is presumably because the overvoltage during charging was low, and lithium was not desorbed in an amount greater than the design standard, so the burden on the negative electrode was small.

[0239] 21 is a diagram comparing the relationship between the amount (wt%) of conductive additive in the positive electrode and the charge / discharge capacity (mAh) between the coin batteries produced in Examples 6 to 14 and Comparative Examples 12 to 21. The horizontal axis indicates the amount of conductive additive added, the vertical axis indicates the capacity, ▲ indicates the charge capacity in the Examples, × indicates the discharge capacity in the Examples, ◯ indicates the charge capacity in the Comparative Examples, and ● indicates the discharge capacity in the Comparative Examples.

[0240] 22 is a diagram comparing the relationship between the amount (wt%) of conductive additive in the negative electrode and the charge / discharge capacity (mAh) between the coin batteries produced in Examples 6 to 14 and Comparative Examples 12 to 21. The horizontal axis indicates the amount of conductive additive added, the vertical axis indicates capacity, ▲ indicates the charge capacity in the Examples, × indicates the discharge capacity in the Examples, ◯ indicates the charge capacity in the Comparative Examples, and ● indicates the discharge capacity in the Comparative Examples.

[0241] The higher the positive electrode potential, the higher the capacity. For this reason, charging is usually performed at a constant voltage to regulate the capacity to a design value. Here, (1) if the positive electrode has a high resistance, the positive electrode itself will have a high charging capacity at a high potential, and ( 2 ) If the negative electrode has high resistance, (battery voltage) = (positive electrode potential) - (negative electrode potential), so high resistance of the negative electrode = negative overvoltage, and the positive electrode potential becomes high, resulting in a high charging capacity.

[0242] Discharge is performed up to a certain end voltage, but with high electrode resistance, the end voltage is cut off early due to voltage drop caused by overvoltage, resulting in low capacity. As a result, the charge / discharge efficiency reflects the state of charge / discharge capacity. Of course, higher efficiency is preferable because it reduces loss of battery capacity. From Figures 21 and 22, it can be seen that the Examples show high discharge capacity with a smaller amount of conductive additive added than the Comparative Examples, and the positive electrode material content per electrode is higher, resulting in a higher capacity per electrode.

[0243] 23 is a diagram comparing the relationship between the amount of conductive additive added in the positive electrode and the initial efficiency and 10 cycle retention rate between the examples and comparative examples for the coin-type batteries produced in Examples 6 to 14 and Comparative Examples 12 to 21. ▲ indicates the initial efficiency in the examples, × indicates the 10 cycle retention rate in the examples, ◯ indicates the initial efficiency in the comparative examples, and ● indicates the 10 cycle retention rate in the comparative examples.

[0244] 24 is a diagram comparing the relationship between the amount of conductive additive added to the negative electrode and the initial efficiency and 10th cycle retention rate between the examples and comparative examples for the coin-type batteries produced in Examples 6 to 14 and Comparative Examples 12 to 21. ▲ indicates the initial efficiency in the examples, × indicates the 10th cycle retention rate in the examples, ◯ indicates the initial efficiency in the comparative examples, and ● indicates the 10th cycle retention rate in the comparative examples.

[0245] Charge / discharge efficiency reflects the state of charge / discharge capacity. Of course, higher efficiency is preferable because it reduces loss of battery capacity. Furthermore, the amount of electricity lost in the battery capacity is consumed by side reactions, and the film formed by the side reactions causes an increase in resistance. When the cycle is repeated, there is no initial loss of battery capacity, but when the electrode overvoltage increases the potential above the normal reaction potential, another side reaction occurs. This side reaction repeatedly creates a film, which further increases resistance and accelerates deterioration in rapid succession, resulting in a continuous decrease in the cycle retention rate.

[0246] 23 and 24, it can be seen that the examples show high efficiency and high retention rate with a smaller amount of conductive additive added than the comparative examples. Therefore, it is presumed that the conductive additive of this embodiment reduces the electrode resistance, suppresses the accumulation of side reactions due to repeated cycles, and allows a high capacity to be maintained even after repeated cycles. [Explanation of symbols]

[0247] 1. Graphene sheet 10 Graphene framework 11 Carbon layer 12 Carbon layer 30 Molded objects 50 Molded objects 100 Carbon Materials 200 Energy storage device (lithium ion battery) 211 Exterior parts 212 Positive electrode 213 Exterior parts 214 Negative electrode 215 Separator 217 Sealing gasket 218 Spring 219 Spacer

Claims

1. A carbon material having a bulk modulus K of 0.7 GPa or less and an average graphene network plane size L of 50 nm or more and 313 nm or less.

2. The carbon material according to claim 1 , wherein the average number of stacking layers n is 1 or more and 6 or less.

3. The carbon material according to claim 1 or 2, wherein the pore diameter d is 5 nm or more and 65 nm or less.

4. 3. The carbon material according to claim 1, wherein the graphene network in-plane nitrogen content N is 0 wt % or more and 10 wt % or less.

5. BET specific surface area S is 400m 2 / g or more 2600m 2 The carbon material according to claim 1, wherein the molecular weight is 1 / g or less.

6. Edge site amount N edge The carbon material according to claim 1 , wherein the molecular weight is 500 μmol / g or less.

7. Edge site specific surface area S edge 30m 2 The carbon material according to claim 1, wherein the molecular weight is 1 / g or less.

8. Pore ​​volume V total is 1.9 cm 3 / g or more 5cm 3 The carbon material according to claim 1, wherein the molecular weight is 1 / g or less.

9. A negative electrode for an electricity storage device, comprising the carbon material according to claim 1 as a conductive assistant.

10. A positive electrode for an electricity storage device, comprising the carbon material according to claim 1 as a conductive assistant.

11. An electricity storage device comprising a positive electrode and / or a negative electrode containing the carbon material according to claim 1 as a conductive assistant.

Citation Information

Patent Citations

  • Ultrahard carbon nanotube and method for manufacturing the same

    JP2003048707A

  • Carbon packing in zeolite nanochannel

    JP2012211069A

  • Microporous carbon-based material, method for producing microporous carbon-based material, adsorbent material and method for occluding hydrogen using microporous carbon-based material

    JP2013199428A

  • Porous carbon material and method of producing the same

    JP2015164889A

  • Porous body and production method of the same, as well as electrode

    JP2017197424A